Pengaruh Rasio Profitabilitas, Likuiditas, dan Solvabilitas Terhadap Nilai Perusahaan: Studi Kasus pada Perusahaan Perbankan di LQ45 Tahun 2019-2023 - Ulfa Laili Nurul Badriyah; Sukristanta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of financial ratios consisting of profitability, liquidity, and solvency ratios on the firm value of banking companies listed in the LQ45 index during the 2019–2023 period. The research method used is a quantitative approach with multiple linear regression analysis. The data used are secondary data from annual financial reports obtained through the official website of the Indonesia Stock Exchange (www.idx.co.id). The results show that the profitability ratio measured by Return on Assets (ROA) has a significant effect on firm value. Meanwhile, the liquidity ratio measured by Current Ratio (CR) and the solvency ratio measured by Debt to Equity Ratio (DER) do not have a significant effect on firm value. These findings have important implications for company management and investors in making strategic financial decisions.